A group‐randomized trial of shared decision making for non‐steroidal anti‐inflammatory drug risk awareness: primary results and lessons learned. Issue 5 (11th June 2014) - Miller, Michael J.; Allison, Jeroan J.; Cobaugh, Daniel J.; Ray, Midge N.; Saag, Kenneth G.
Abstract Rationale, aims and objectives Frequent use and serious adverse effects related to non‐steroidal anti‐inflammatory drugs (NSAIDs) underscore the need to raise patient awareness about potential risks. Partial success of patient‐ or provider‐based interventions has recently led to interest in combined approaches focusing on both patient and physician. This research tested a shared decision‐making intervention for increasing patient‐reported awareness of NSAID risk. Methods A group randomized trial was performed in Alabama from 2005 to 2007. Intervention group doctor practices received continuing medical education (CME) about NSAIDs and patient activation tools promoting risk assessment and communication during visits. Comparison group doctor practices received only CME. Cross‐sectional data were collected before and after the intervention. Generalized linear latent and mixed models with logistic link tested relationships among the intervention, study phase, intervention by study phase interaction and patient‐reported awareness of risks with either prescription or over‐the‐counter (OTC) NSAIDs. Results Three hundred and forty‐seven patients at baseline and 355 patients at follow‐up participated in this study. The intervention [adjusted odds ratio (AOR) = 0.74, P = 0.248], follow‐up study phase (AOR = 1.31, P = 0.300) and intervention by study phase interaction (AOR = 0.98, P = 0.942) were not significantly associated with patient‐reported awareness of any prescription NSAID risk. Follow‐up study phase was associated with increased odds of reporting any OTC NSAID risk awareness (AOR = 2.99, P < 0.001), but the patient activation intervention and intervention by study phase interaction were not significantly associated with patient‐reported awareness of any OTC NSAID risk (AOR = 0.98, P = 0.929; AOR = 0.87, P = 0.693, respectively). Conclusions Our point‐of‐care intervention encouraging shared decision making did not increase NSAID risk awareness.